2020
DOI: 10.1186/s12879-020-05591-6
|View full text |Cite
|
Sign up to set email alerts
|

Time-trend of hospitalizations for anogenital warts in Veneto region in the HPV vaccination era: a cross sectional study (2007–2018)

Abstract: Background Human papillomavirus (HPV) is a common sexually transmitted pathogen and the cause of several cancers and of anogenital warts. With this study, we estimated the trend of hospitalizations for anogenital warts (AGWs) in the Veneto region (Italy) from 2007 to 2018. Methods The analysis included all the hospital discharge records of public and accredited private hospitals occurred in Veneto residents in the timespan 2007–2018. The ICD9-CM code 078.11 considered were those associated with condyloma acum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In contrast and coherently to what was reported in other countries, Genital Warts, caused by the papillomavirus, showed a slight decrease over time [ 30 ]. This is a reduction that could most likely be a direct and visible effect of the mass HPV vaccination strategy adopted in our country along with many other countries in Europe [ 40 , 41 , 42 , 43 , 44 , 45 ], which deserves further investigation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast and coherently to what was reported in other countries, Genital Warts, caused by the papillomavirus, showed a slight decrease over time [ 30 ]. This is a reduction that could most likely be a direct and visible effect of the mass HPV vaccination strategy adopted in our country along with many other countries in Europe [ 40 , 41 , 42 , 43 , 44 , 45 ], which deserves further investigation.…”
Section: Discussionsupporting
confidence: 76%
“…As only symptomatic patients visit EDs, available clinical studies are frequently focused on a single group or on narrow groups of infections [ 25 , 26 , 27 , 28 ], mostly identified through International Classification of Diseases (ICD) codes [ 19 , 29 , 30 ] and they often pool both adolescents and young adults together [ 27 , 31 ] despite considerable differences.…”
Section: Introductionmentioning
confidence: 99%
“…The notable reduction in hospitalizations is predominantly attributed to a substantial decline among females, dropping from 20.4 per 100,000 to 10.8 per 100,000. In contrast, males showed a marginal increase in hospitalization rates, although it did not reach statistical significance [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second study conducted in Veneto showed that HPV vaccination coverage rates of around 70% in girls were associated with a significant decrease in hospitalization rates for anogenital warts (AAPC: -6.1%; 95% CI: -8.4; -3.7) in women 17 to 46 years old in the years from 2007 to 2018. Interestingly, hospitalization rates for anogenital warts in men increased during the same period (AAPC: 3.8%; 95% CI: 1.2; 6.4), a change driven only by rising numbers of cases of anal warts [70].…”
Section: Italymentioning
confidence: 99%
“…Not all types of HPV have the same carcinogenic potential and there are fortunately just a few responsible for most cases of disease. The World Health Organization's International Agency for Research on Cancer (IARC) lists (Table 1 ): HPV types 16,18,31,33,35,39,45,51,52,56,58 and 59 in group 1, "Carcinogenic to humans"; types 30,34,69,85,97,26,53,66,67,70,73 and 82 in group 2B, "Possibly carcinogenic to humans"; and types 6 and 11 in group 3, "Not classifiable as to its carcinogenicity to humans" [13]. Although HPV types 5 and 8 are listed in group 2B, their carcinogenic effect is related to a rare autosomal recessive hereditary skin disorder, epidermodysplasia verruciformis [14].…”
Section: Epidemiology Of Hpvmentioning
confidence: 99%